2020
DOI: 10.1155/2020/7167243
|View full text |Cite
|
Sign up to set email alerts
|

Research on Dynamic Path Planning of Wheeled Robot Based on Deep Reinforcement Learning on the Slope Ground

Abstract: The existing dynamic path planning algorithm cannot properly solve the problem of the path planning of wheeled robot on the slope ground with dynamic moving obstacles. To solve the problem of slow convergence rate in the training phase of DDQN, the dynamic path planning algorithm based on Tree-Double Deep Q Network (TDDQN) is proposed. The algorithm discards detected incomplete and over-detected paths by optimizing the tree structure, and combines the DDQN method with the tree structure method. Firstly, DDQN a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 13 publications
(11 reference statements)
0
7
0
Order By: Relevance
“…Each attribute of employment data is generalized, and the original data set of college students' employment is divided into a conditional attribute set and a target attribute set. e goal of generalization is to divide the interval of continuous employment attributes in the original data set of college students' employment into many cells, each with a discrete symbol [25]. In order to create a decision-making system, match the nodes in the hierarchical classification model with the conditional attributes of the employment data set to be classified.…”
Section: Construction Of Predictive Factor Model Of Subjectivementioning
confidence: 99%
“…Each attribute of employment data is generalized, and the original data set of college students' employment is divided into a conditional attribute set and a target attribute set. e goal of generalization is to divide the interval of continuous employment attributes in the original data set of college students' employment into many cells, each with a discrete symbol [25]. In order to create a decision-making system, match the nodes in the hierarchical classification model with the conditional attributes of the employment data set to be classified.…”
Section: Construction Of Predictive Factor Model Of Subjectivementioning
confidence: 99%
“…A sale price near to one indicates that long-term incentives are weighted similarly to short-term rewards, but a reduced interest factor indicates that the individual is myopic and only cares about prizes that are due this month in Eq. (2).…”
Section: Dqn Algorithmmentioning
confidence: 99%
“…The autonomous robots use a tool path to choose the best path from point A to point B without colliding with any barriers [1]. The proposed approach for mobile robots is in the face of increasing scientific and technological breakthroughs is currently confronted with a complicated and dynamic world [2]. The traditional path planning algorithms lack certain salient merits such as least working cost and minimal processing time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lei et al found that adding the Q-Learning algorithm to the reinforcement learning path enhances the ability of robots to dynamically avoid obstacles and local planning in the environment (Lei et al, 2018 ; Liu et al, 2019 ). Wang et al found that compared with Distributed DQN (DDQN) algorithm, the Tree Double Deep Network (TDDQN) has the advantages of fast convergence speed and low loss (Wang P. et al, 2020 ). By using a neural network to strengthen the learning path planning system, Wen et al suggested that the mobile robot can be navigated to a target position without colliding with any obstacles and other mobile robots, and this method was successfully applied to the physical robot platform (Wen et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%